Potential of Hydropower-Based Renewable Energy in Cipunegara Watershed - Yakub Siahaan; Dede Rohmat; Ahmad Yani; Lili Somantri (Department of Geography Education, University of Jember, 2023)
Developing new and renewable energy (NRE) is a sustainable solution to the current complexity associated with population growth and environmental problems. Some developed countries have recognized renewable energy development as a substitute for non-renewable energy such as coal, petroleum, and natural gas. Therefore, this study employed the geospatial approach scheme to identify the NRE potential in the Cipunegara watershed. This was achieved using regional research with a spatial approach and considering five locations in the upstream area of the Cipunegara watershed. Data were collected through observation, consultation with experts, and map interpretation, and analyzed using descriptive statistics. The results showed that only location 2 had a significant potential to be used in building a dam to generate electrical energy. This study was based on several aspects such as hydrology, morphology, topography, meteorology, erosion, geology, and land use. The results were derived from empirical data and geospatial modeling, and expected to serve as a significant reference for the central government in developing EBT as the tangible manifestation of the Sustainable Development Goals 2030 program and the implementation of the national research master plan 2017-2045.